Gender analysis of Persian staying-at-home messages during Covid-19 pandemic - S. Shafiei (Taḥqīqāt-i Farhangī-i Īrān)
In the Iranian family sociology, the dominant approach is based on this general idea that the family is the center of patriarchy. Based on this view, women at home are in subjugation and under male dominance. To support this idea, a lot of researches have been conducted in recent years. However, the present study does not seek to identify the patterns of female subjugation; rather it is in the process to identify the patterns of their resistance to male dominance within the home. As such, the study seeks to answer the question as how women use "culture" as a tool of resistance as well as to change the balance of power in the family. In this regard, 36 married women were interviewed. Findings showed that women use the strategies such as "struggle for meaning", "reverse decoding", "resistance to gender stereotypes", "resistance through tradition" and "appearance of obedience but hidden resistance within family" to resist the male dominance. Through these, they try to control male power in the home and balance it accordingly. Various resistance strategies indicate that women’s “resistance sources" in the family are numerous, which take place in different domains and in different ways.